Mito-Tempo improves acrosome integrity of frozen-thawed epididymal spermatozoa in tomcats - Ali Hassan, Hiba; Banchi, Penelope; Domain, Guillaume; Vanderheyden, Leen; Prochowska, Sylwia; Nizański, Wojciech; Van Soom, Ann (Frontiers in Veterinary Science, 2023)
In tomcats, epididymal spermatozoa provide an additional source of male gametes available for cryopreservation. Whereas this procedure is feasible, survival rate and motility of epididymal cat spermatozoa are both low after thawing. Cryopreservation is known to induce oxidative stress in spermatozoa, with mitochondria and the plasma membrane being the two major generation sites, and an imbalanced presence of free radicals is a possible cause for this low survival rate. Different antioxidants have been tested before for their effect on cryopreserved cat spermatozoa, with varying results. Here, we used Mito-Tempo, which is a synthetic mitochondria-targeted antioxidant and a specific scavenger of the mitochondrial superoxide system. By supplementing Mito-Tempo to the freezing extender, we aimed to improve sperm quality of frozen-thawed cat epididymal spermatozoa. Epididymal spermatozoa obtained from twelve tomcats were assessed for motility, concentration, and morphology. Prior to freezing, samples were diluted in TRIS buffered extender with egg yolk and glycerol and divided into five aliquots supplemented with 0 (control), 0.5, 5, 50, and 100 μM of Mito-Tempo. After thawing, sperm motility, concentration, morphology, plasma membrane integrity, acrosome integrity, and mitochondrial membrane potential were evaluated Friedman rank sum test with Bonferroni post-hoc test was used to determine statistical in-between group differences in post-thaw semen parameters. The results indicated a slight improvement in acrosome integrity across all groups that were supplemented with Mito-Tempo, with the group that received 5 µM of Mito-Tempo showing the greatest improvement ((median of 67.99%, IQR of 5.55) compared to the control group (median of 65.33%, IQR of 7.75; P=0.05)). For all other sperm parameters, no significant differences (P > 0.05) were detected between different Mito-Tempo concentrations. These findings highlight the protective effect of Mito-Tempo on acrosome integrity and suggest that 5 µM is the most effective concentration for maintaining acrosome integrity. Since Mito-Tempo had shown a positive effect on multiple sperm parameters in other species, such as men, boars, roosters, rams, and bulls, we need to conclude that species-specificity may play a role here.